Functional finishes for textiles : improving comfort, performance and protection - Almeida, Laurindo (Woodhead publishing in textiles ;, 2015)
Functional finishes for textiles reviews the most important fabric finishes in the textile industry. It discusses finishes designed to improve the comfort and other properties of fabrics, as well as finishes which protect the fabric or the wearer. Each chapter reviews the role of a finish, the mechanisms and chemistry behind the finish, types of finish and their methods of application, application to particular textiles, testing and future trends. Describes finishes to improve comfort, performance, and protection of fabric or the wearerExamines the mechanisms and chemistry behind different type.